La transición desarmada : objetores, política y prensa en la transformación de las Fuerzas Armadas en la España democrática - Carmen Gordon-Nogales (Amnis)
With the end of obligatory military service in January 2001, we can consider that the process of adjustment of the armies of the Franco period to the new European and international situation — one of the most complex in the Spanish transition to democracy — comes to the end. During this process, which generates unprecedented media interest, the conscientious objection movement played a very important role. Its mobilizations will have a significant impact throughout the media, and this will lead to a growing interest in military questions on the part of society, which had been kept at a distance during its recent history. After giving a brief description of the historical background to conscientious objection, this article deals with the analysis of the subjects and categories which the national press uses in the debate on the professionalization of the armies. We will also take into account how this debate tends to reinforce the legitimacy that the military institution acquired throughout the transition to democracy.